Unravelling soluble immune checkpoints in chronic lymphocytic leukemia: Physiological immunomodulators or immune dysfunction - Landeira-Viñuela, Alicia; Arias-Hidalgo, Carlota; Juanes-Velasco, Pablo; Alcoceba, Miguel; Navarro-Bailón, Almudena; Pedreira, Carlos Eduardo; Lecrevisse, Quentin; Díaz-Muñoz, Laura; Sánchez-Santos, José Manuel; Hernández, Ángela-Patricia; García-Vaquero, Marina L.; Góngora, Rafael; et al. (Frontiers in Immunology, 2022)
Chronic lymphocytic leukemia (CLL) is a lymphoid neoplasm characterized by accumulation of mature B cells. The diagnosis is established by the detection of monoclonal B lymphocytes in peripheral blood, even in early stages (monoclonal B cell lymphocytosis -MBLhi-), and its clinical course is highly heterogenous. In fact, there are well-characterized multiple prognostic factors, which are also related to the observed genetic heterogenicity, such as immunoglobulin heavy chain variable region (IGHV) mutational status, del17p, TP53 mutations, among others. Moreover, a dysregulation of immune system (innate and adaptive immunity) has been observed in CLL patients, with strong impact on immune surveillance and consequently on the onset, evolution, and therapy response. In addition, the tumor microenvironment is highly complex and heterogenous (i.e.: matrix, fibroblast, endothelial cells, immune cells) with is playing a critical role in the evolution of CLL. Then, in this study, it has been systematically evaluated a quantitative profile of 103 proteins (cytokines, chemokines, growth/regulatory factors, immune checkpoints and soluble receptors) in 67 serum samples (57 CLL and 10 MBLhi). Also, it was deciphered differential profiles of soluble immune factors that discriminate between MBLhi vs. CLL (sCD47, sCD27, sTIMD-4, sIL-2R and sULBP-1), disease progression (sCD48, sCD27, sArginase-1, sLAG-3, IL-4, sIL-2R) or among profiles correlated with other prognostic factors, such as IGHV mutational status (CXCL11/I-TAC, CXCL10/IP-10, sHEVM, sLAG-3). These results are opening a hallmark to explore the role of soluble immune checkpoints as a promising source of biomarkers in CLL, among to provide novel insights on the immune suppression process and/or dysfunction, mostly on T cells, in combination with cellular balance disruption and microenvironment polarization leading to tumor scape.